2023
DOI: 10.1186/s13677-023-00516-5
|View full text |Cite
|
Sign up to set email alerts
|

Orchestration in the Cloud-to-Things compute continuum: taxonomy, survey and future directions

Amjad Ullah,
Tamas Kiss,
József Kovács
et al.

Abstract: IoT systems are becoming an essential part of our environment. Smart cities, smart manufacturing, augmented reality, and self-driving cars are just some examples of the wide range of domains, where the applicability of such systems have been increasing rapidly. These IoT use cases often require simultaneous access to geographically distributed arrays of sensors, heterogeneous remote, local as well as multi-cloud computational resources. This gives birth to the extended Cloud-to-Things computing paradigm. The e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 74 publications
0
2
0
Order By: Relevance
“…As discussed in [3][4][5], auto-scaling algorithms are diverse and involve various components at the infrastructure, platform and software levels. The classification, however, differs from our viewpoint.…”
Section: Related Workmentioning
confidence: 99%
“…As discussed in [3][4][5], auto-scaling algorithms are diverse and involve various components at the infrastructure, platform and software levels. The classification, however, differs from our viewpoint.…”
Section: Related Workmentioning
confidence: 99%
“…Five review articles [2][3][4][5][6] and three survey articles [7][8][9] were found that research similar aspects of the IECC. Kampars et al [3] reviewed the application layer communication protocols that can be used for interconnecting the layers of the IECC.…”
Section: Related Workmentioning
confidence: 99%
“…In addition, they analyzed the directions in which applications can benefit from this computing paradigm. In order to provide a taxonomy for orchestration in the cloud-to-things compute continuum, Ullah et al [6] reviewed existing state-of-the-art research on orchestration in this field. In addition, they proposed a high-level conceptual framework of orchestration.…”
Section: Related Workmentioning
confidence: 99%